TRANSPORT AND SUSTAINABLE DEVELOPMENT - IMPACT OF THE SYSTEMS OF POPULATION MOBILITY AND GOODS ON THE ECOLOGICAL FOOTPRINT IN GALICIA (SPAIN) - Fernando González Laxe; Federico Martín Palmero; Fernanda Miguélez Pose (European Regional Science Association (ERSA), 2005)
Although the calculation of indicators of sustainable development is increasing on both national and global levels, its implementation to the regional analysis is still very incipient, especially regarding those indicators that are considered as measures of the strong sustainability. Some recent researches have determined that the ecological footprint in Galicia reaches 7.01 hectares per capita, much higher than the Spanish one (4.90) or the world average (2.18). Among others, one of the main reasons of this figure for this indicator in this specific Spanish region is the excessive contribution of the footprint of energy (2.18 hectares per capita), and, in this group, the significant weight of the means and methods of transport that are used. This document deals with the analysis of this specific component of the ecological footprint in Galicia from different perspectives: first, the influence of using an intensive transport of goods on the combustion of fossil fuels to the detriment of other more sustainable transports; secondly, the mobility habits of the population (both acquired or imposed as there are no alternatives); and, finally, some reflections about the structural reasons of this behaviour.
Keywords: 330